Role of Intraoperative Radiographs in the Surgical Treatment of Adolescent Idiopathic Scoliosis. Issue 2 (March 2016) - Vidal, Christophe; Ilharreborde, Brice; Queinnec, Steffen; Mazda, Keyvan
Abstract : Background: One of the main goals of scoliosis surgery is to obtain a balanced fused spine. Although preoperative planning remains essential, intraoperative posteroanterior radiographs are the only available tool during the procedure to verify shoulder and coronal spinal balance and, if necessary, adjust the construct. The aim of this study was to quantify the direct influence of intraoperative radiographs on the surgical procedure itself during correction of adolescent idiopathic scoliosis. Methods: Retrospective analysis of prospectively collected data on a monocentric cohort of adolescent idiopathic scoliosis patients undergoing corrective surgery. A total 148 consecutive patients operated in the same department following the same validated preoperative planning method were included in this prospective radiologic study. The mean follow-up averaged 33 months. Frontal Cobb angles, T1 tilt, shoulder tilt, iliolumbar angle, and frontal balance were measured and compared on intraoperative, early postoperative, and latest follow-up radiographs. Any intraoperative modification of the correction performed after analysis of the intraoperative radiograph were recorded. Results: The analysis of all radiologic parameters was possible in 90.5% of the cases. In 9.5% of the cases, shoulders could not be properly distinguished. Significant modifications on the upper thoracic curve to correct T1 tilt or shoulder balance were performed in 29% of the patients, and changes at the distal levels were recorded in 19%, underlining planification imperfections. On postoperative standing radiographs, the average coronal parameters were neutral, without loss of correction at follow-up. Conclusions: Intraoperative radiographs remain necessary to ensure compensation of the shortcomings of the modern preoperative planification method. Level of Evidence: Level IV.